La prehistoia de los medios - Arizmendi, José Vicente; Pontificia Universidad Javeriana (2009)
Reseña del libro: Zielinski, S. (2006). Deep Time of the Media: Toward an Archaeology of Hearing and Seeing by Technical Means. Trad. del alemán: Gloria Custance. Cambridge- Londres: mit Press. 375 páginas. isbn: 0-262-24049.